Affective Relationships Among Siblings in a Situation of Institutional Care - Carvalho e Silva, Jonas (2023)
The purpose of this article is to identify the relationships of affection that exist between children/adolescents institutionalized in the same shelter. Data collection was carried out in two sisters hosted in Brasília-DF, through field notes, documentary analysis script, theme-story drawing, collage and semi-structured interviews. The indicators arouse from the results, which guided the organization of two of the sense zones, based on the methodology developed by Gonzalez Rey: a) The family of origin and the affective memories; b) Institutionalization and affection in the fraternal relationship. The importance of the sibling group was identified for the establishment of the sense of security, protection and pre-disposition for more positive and resilient attitudes.